The Effect of Implementation of IFRS 17 Accounting Standards on Audit Delay in Insurance Companies Listed on the Indonesia Stock Exchange - Maan, Marsela Yunita; Pabulo, Azfa Mutiara Ahmad (SIMAK, 2024)
The effect of IFRS 17 implementation on audit delay in insurance companies listed on the Indonesia Stock Exchange. Audit delay, which can affect the quality of financial statements, is expected to increase due to new complexities in insurance contract accounting. The objective is to understand how IFRS 17 impacts the completion time of the audit process. The dependent variable is audit delay, while the independent variables include operational complexity, profitability (ROA), and financial statement presentation. The results of the analysis show that operational complexity and profitability have no significant effect on audit delay, with significance values ​​of 0.225 and 0.105, respectively. In contrast, the quality of financial statement presentation has a significant effect (0.036), affecting the efficiency of the audit process. This finding emphasizes the importance of improving the quality of financial statements to minimize audit delay. The conclusion is that operational complexity and company profitability have no significant effect on audit delay. In contrast, the quality of financial statement presentation has a significant effect. Good reports make it easier for auditors and speed up the audit process. Poor report quality slows down verification and evidence collection, increasing audit delay.